How do you solve 3x ^ { 3} + 18= x ( 2x + 27)?

2 Answers
Jun 15, 2017

x = 3, -3, 2/3

Explanation:

First multiply out the bracket on the LHS of the equation.

3x^3 + 18 = 2x^2 + 27x

Rearrange to get a cubic equation.

3x^3 + 18 - 2x^2 - 27x = 0

3x^3 - 2x^2 - 27x + 18 = 0

Now find a number that can be substituted into x that will make the equation equal zero.

When x = 3, the equation is zero.

We now have a factor and now we can factorise the equation.

(x-3)(3x^2+7x-6) -> (x-3)(3x-2)(x+3)

Now you can find the answers for x.

x = 3, -3, 2/3

Jun 15, 2017

x = 3, -3, 2/3

Explanation:

I would start by distributing the x on the right side of the equal sign.

3x ^ { 3} + 18= 2x^2 + 27x

Get everything to one side, I moved everything to the left side. Do this by subtracting the terms on the left side. You get

3x ^ { 3} + 18 -2x^2 -27x = 0

Then reorder into standard form (decrease exponents)

3x^3 -2x^2 -27x + 18 = 0

When ever you have 4 terms, it is usually a factoring by grouping problem. Put parenthesis around the first two and the last two terms.
(3x^3 -2x^2) (-27x + 18 )= 0

Look for what can be factored out of the first grouping: x^2
Look for what can be factored out of the second groping: -9

The first grouping now looks like x^2(3x-2)
The second grouping now looks like -9(3x-2)

Notice the terms in the parenthesis are the same.

your problem now looks like:
x^2 (3x-2) -9(3x -2) = 0

Now when you factor by grouping you put the two terms in front of the parenthesis together in front of the set of parenthesis.

(x^2 - 9)(3x-2) = 0

Now set each sit of parenthesis equal to zero and solve

#(x^2-9) = 0 and (3x-2) =0.

I recognized the first terms as the difference of two squares which means it can be easily factor
(x^2-9) -> (x+3)(x-3) = 0

so x could be +3 or -3.

Don't forget to solve the second equation 3x -2 =0
Add two to both sides, then divide by 3.

x =2/3

x = 3, -3, 2/3